Sex‑specific associations between multiple hormone axes and dynapenic obesity in middle‑aged and older patients with type 2 diabetes - Di Yu; Qin Ou; Bo Xie; Yinghao Li; Kun Liao; Rong Li; Mei Mei; Bo Zhou (Medicine, 2026)
Accumulating evidence indicates that hormones play a critical role in the pathogenesis of dynapenic obesity (DO), although the precise relationships and underlying mechanisms remain elusive. This study aimed to investigate sex-stratified associations between multiple hormones and prevalence of DO in type 2 diabetes mellitus (T2DM) populations. In this cross-sectional study of 557 T2DM patients, body composition was assessed by dual-energy X-ray absorptiometry, and hormones from pituitary-target gland axes and the vitamin D system were also tested. Moreover, demographic data, nutritional and inflammatory status, comorbidities and diabetic complications were collected. On the basis of sex-specific cutoff values for grip strength and body fat percentage, the participants were categorized into 4 groups: nondynapenic/nonobese (ND/NO), nondynapenic/obese (ND/O), dynapenic/nonobese (D/NO), and DO. Ordinal logistic regression was used to analyze the associations between the progression of low muscle strength and concurrent adipose accumulation and hormonal profiles. Among the enrolled diabetic adults, the incidence rates of DO in males and females were 20.6% and 37.9%, respectively. Compared with ND/NO patients, DO patients typically exhibit advanced age, poorer nutritional status, reduced gait speed and low-grade inflammation. Moreover, the 25 (OH) D level in males with DO was significantly lower than that in the ND/NO group, and even after full adjustment, 25 (OH)D remained significantly inversely associated with DO progression (OR = 0.98, 95% CI: 0.96–1.00, P < .05); however, in females, the serum dehydroepiandrosterone level also decreased (OR = 0.99, 95% CI: 0.99–1.00, P < .05), whereas the parathyroid hormone level increased (OR = 1.01, 95% CI: 1.00–1.02, P < .05) with increasing DO. DO is relatively common in individuals with T2DM and is closely related to aging, nutritional and inflammatory status, and sex-specific hormonal differences.